G33(P) Referral guidelines for paediatric outpatients from primary care. (24th May 2017) - Mead, A; Marder, E; Wells, L; Corker, E; James, N; Sands, R
Abstract : A review of outpatient referrals to secondary care paediatrics (community and hospital), was performed in 2012 due to concerns from the local children's health network regarding the quality and variation in outpatient referrals from primary to secondary care. A referral database was used to identify referrals to secondary care paediatrics that could have been managed in primary care, and identify the most commonly referred conditions. 88 randomly selected referrals were reviewed by an experienced general practitioner and a consultant paediatrician. 7/44 community and 12/44 hospital referrals were assessed as being suitable for management in primary care (21.6%), The array of conditions was broad. Failure to reassure parents was deemed an appropriate referral reason. This led to a recommendation to develop referral guidelines for paediatric outpatients from primary care. They were developed through workshops attended by paediatricians from both local hospitals and community paediatric services, children's leads from local CCG's with review and endorsement by the Nottingham/Nottinghamshire Children and Young People's Health Network which includes clinicians from all local Children's health providers, public health professionals, and commissioners. The guidelines include advice on 100 conditions/presentations. Alongside guidance on when to refer and with what urgency, the document links to national and local condition specific guidelines on management, suggests alternatives to referral, and provides links to parent information. The guidelines have been used since November 2015 – by GPs when considering referring and by paediatricians when 'vetting' referrals. After a year, the rejected referral rate has increased from 8% (November 2015) to 19% (November 2016) despite total referrals remaining relatively constant (552 in November 2015, 575 in November 2016). This suggests that referral guidance has not yet changed GP referral patterns The guidance has been updated and will be re-launched in January 2017 with presentations planned at GP learning events. It will be published on the Nottingham care navigator, with links from various other resources – including the service information on the electronic referral system. Audit of use and impact, and arrangements for regular update are planned. The presentation will include examples of the referral guidance.